A Study Causality Testing between Public Expenditure and Economic Growth in Oman - Tamilselvan, M.; Manjula, V. (Advances in Social Sciences Research Journal, 2019)
The incremental growth of GDP is very significant to all the nations in order to create adequate employment opportunities and implement various welfare and developmental schemes. Therefore, the priority of the government is to enhance the growth by enriching investment and allocating funds to various schemes. Among the various factors which determine the growth, public expenditure is one of the significant factors. In this direction, the current study has made an effort to identify the causal relationship between GDP and Public Expenditure in Oman using data for 42 years between 1974-2015. The data has been analyzed using Johansen Cointegration Test, Vector Error Correction Model and Wald test. The findings of the study revealed that there is unidirectional causality running from Public Expenditure towards GDP and supports the Keynesian (1936) approach which emphasize that the spend- revenue hypothesis.